Preliminary study of marine debris from selected beaches in Malaysia - Harith, Siti Suhaila; Osman, Anas Iylia; Shamsholanwar, Nurul Afiqah; Shahul Hamid, Fauziah (Universiti Teknologi MARA (UiTM), 2024)
Beach pollution is rising due to Malaysia's rapid urbanisation and population growth. Therefore, the objectives of the study are to identify the type and abundance of marine debris and to determine people's awareness of marine debris. Pantai Redang, Sekichan, Selangor, and Pantai Senok, Kelantan, were chosen. Samples were taken in 2018. The study is divided into two principal types of assessment which are coastal litter assessment and through questionnaires. At Pantai Redang and Pantai Senok, 1086 and 1429 marine debris of diverse forms were gathered. On both beaches, HDPE is the most common macrodebris. Both receive less than 1 debris unit per m2. In addition, Pantai Redang and Pantai Senok recorded at least 6 and 3 grams of debris per 1 m2 area. The two microplastics on both beaches weighed less than 0.001 grams. Less than 9 out of 100 survey respondents intend to fully accept responsibility for marine debris. Chi-square analysis proves that there are significant differences between the factors that cause marine debris at p=0.000. Marine debris is present on both beaches due to too few litter containers and too many single-use products. In conclusion, the increasing volume of marine garbage is frightening and requires action to prevent marine ecological degradation